(untitled) (Nigerian Journal of Physiological Sciences, 2025)
Introduction: Neem (Azadirachta indica A. Juss, Meliaceae) is a popular medicinal plant widely sought for its antipyretic, antimalarial, anti-inflammatory, antidiabetic, and antibacterial properties, among others. Methods: Cold-pressed oil from neem seed (NOil) and its cyclohexane-methanol extract (NOHM) were evaluated for their effects on α-amylase and α-glucosidase activities in vitro. Also, NOil (75, 150, and 200 mg/kg) and NOHM (200, 400, and 800 mg/kg) were orally administered to normal experimental rats for 30 days, following which the lipid profile, antioxidant status, and serum and tissue indices of hepatic, renal, and cardiac damage were evaluated. Results: NOHM caused significantly higher (p<0.05) α-glucosidase inhibition than NOil. Respectively, the α-amylase and α-glucosidase inhibitory effects of NOil (IC50 = 4.88 ± 0.38 µg/mL and 74.54 ± 25.26 µg/mL) and NOHM (5.00 ± 0.22 µg/mL and 14.17 ± 5.14 µg/mL) were superior to that of acarbose (9.67 ± 0.09 µg/mL and >150 µg/mL). NOHM produced a stronger hypoglycemic effect than NOil. However, no biochemical alteration of toxicological importance was caused by either following subacute administration to animals as the organ-body weight ratio and serum and tissue indicators of organ damage were not adversely altered. Conclusion: The present findings support the safety of NOil and NOHM at the evaluated dosages. The effect of both oil and extract on key carbohydrate-metabolizing enzymes could partly explain the biochemical rationale underlying the popular ethnomedicinal application of the seed in diabetic management. Keywords: Neem oil; toxicity; cyclohexane-methanol extract; α-amylase; α-glucosidase; in vitro